ARABIC TEACHING FOR UNDERGRADUATE IN INDONESIA “THE EXPERIENCE OF UIN MAULANA MALIK IBRAHIM MALANG IN THE INTENSIVE PROGRAM FOR TEACHING ARABIC” - Salah, Munair Yusaf Abdal Hafiz; Mufidah, Nuril (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Islamic State University Maulana Malik Ibrahim of Malang (UIN Maulana Malik Ibrahim Malang) has been interested in teaching Arabic since its inception. It is based on its philosophy of Islamic education, which is based on Arabic, a basic knowledge of understanding Islamic knowledge and sciences.The university established the intensive Arabic program to achieve Arabic education according to a specialized scientific method in 1997. The goal of this program is to develop the linguistic skills of the new students in the university until they can access the Arabic sources that have written Islamic sciences to develop their culture and develop their sciences.And the approach in this paper are study and descriptive analytical. The listening skill is the focus on the teaching of ashwat. This program use Al-Arabiyah li An-Nasyiin and Al-Arabiyah Baina Yadaika. These two books are different, Al-Arabiyah li An-Nasyiin is interested in teaching sounds such as Al-Arabiyah Baina Yadaika, although it is presented in terms of shortcomings and great divergence. The student complete the ashwat (phonatic) . ; they need to complete two books and arranging the ashwat (phonatic) . is not gradual according to the principle of easy and difficulty, but they neglected to mention some ashwat (phonatic) . and training them. The teaching of ashwat (phonatic) . in this program complains of a schematic imbalance and its overlapping material and the educational units determined from the two books do not agree with the educational plan of the ashwat (phonatic) . that were written by the two books. Therefore, the researcher found that many teachers do not know the ashwat (phonatic) .